Contested professional role boundaries in health care: a systematic review of the literature - Olivia King; Susan A Nancarrow; Alan M Borthwick; Sandra Grace (Journal of Foot and Ankle Research, 2015)
Abstract Background Across the Western world, demographic changes have led to healthcare policy trends in the direction of role flexibility, challenging established role boundaries and professional hierarchies. Population ageing is known to be associated with a rise in prevalence of chronic illnesses which, coupled with a reducing workforce, now places much greater demands on healthcare provision. Role flexibility within the health professions has been identified as one of the key innovative practice developments which may mitigate the effects of these demographic changes and help to ensure a sustainable health provision into the future. However, it is clear that policy drives to encourage and enable greater role flexibility among the health professions may also lead to professional resistance and inter‐professional role boundary disputes. In the foot and ankle arena, this has been evident in areas such as podiatric surgery, podiatrist prescribing and extended practice in diabetes care, but it is far from unique to podiatry. Methods A systematic review of the literature identifying examples of disputed role boundaries in health professions was undertaken, utilising the STARLITE framework and adopting a focus on the specific characteristics and outcomes of boundary disputes. Synthesis of the data was undertaken via template analysis, employing a thematic organisation and structure. Results The review highlights the range of role boundary disputes across the health professions, and a commonality of events preceding each dispute. It was notable that relatively few disputes were resolved through recourse to legal or regulatory mandates. Conclusions Whilst there are a number of different strategies underpinning boundary disputes, some common characteristics can be identified and related to existing theory. Importantly, horizontal substitution invokes more overt role boundary disputes than other forms, with less resolution, and with clear implications for professions working within the foot and ankle arena.